New Training Requirement for Utility Employees. Issue 5 (1st May 2013) - Spence, Shannon; Herndon, Christine; Taschereau, Amber
Abstract : If you use, manage, or handle hazardous materials, chances are you have seen a Material Safety Data Sheet (MSDS). MSDSs serve as a mechanism to communicate the hazards of specific chemicals in order to comply with 29 CFR 1910.1200. Although an MSDS includes standard sections, those sections have some flexibility in how the manufacturer classifies the chemical and health statements. As a result, the same chemical could be labeled differently by multiple companies.